Preservation of Rural Characteristics in Urbanized Villages - Hadas Shadar (Land)
The aim of this article is twofold: to identify physical rural characteristics that persist after villages undergo urbanization, and to propose an appropriate planning “language” for preserving them. The article contributes to the literature, as current studies addressing rural preservation focus on the early stages of urbanization and on several physical preservation recommendations, most of which emphasize residential buildings alone. The article addresses the case study of Jewish villages established in pre-statehood Palestine. These comprise dozens of settlements planned based on European models and built from the late nineteenth century until World War I. Most underwent urbanization and evolved into towns or large cities. The study identifies rural characteristics that have endured and explores how they can be preserved through contemporary planning. The findings reveal that in all major cities examined, large open areas have been preserved within the former farmyards located behind the pioneers’ residential buildings. The article argues that beyond the preservation of original structures, historical trees, and gardens, particular importance should be placed on preserving these former farmyards as intra-urban open spaces. Maintaining sightlines from the streets toward these areas and enabling movement into them will help retain the rural features of the former villages.